DETECTION OF TOXOPLASMOSIS IN CATS AND SHEEP - Kallo, Osama J. (The Iraqi Journal of Veterinary Medicine, 2021)
Thirty-three fecal samples from cats were examined for the presence of Toxoplasma oocysts, and another 33 serum samples from these cats were subjected for Latex agglutination test & indirect immunofluorecent antibody test. Also 80 serum samples from ewes were subjected to the same serological tests. The study indicated that the prevalence of Toxoplasma oocysts in cats was 27.3%. Higher rates of antibody titer (68%) were observed in cats tested with latex test. Infection in young cats was higher than in adults. Sixty percentage of ewes were sero-positive with Latex test, but only 35% were sero-positive with IFAT, higher prevalence of antibody titers was observed in sheep from the three locations of Iraq. Ewes that had recurrent abortion showed higher prevalence in both tests than non aborted ewes.